1968
DOI: 10.1128/jb.96.4.1079-1088.1968
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Synthesis inSalmonella typhimurium: Requirement for Ribonucleic Acid Synthesis

Abstract: The micro-complement-fixation assay has been demonstrated to be a sensitive assay for flagella which occur in nanogram amounts. By use of this assay, it was found that flagellar synthesis occurs during starvation of Salmonella typhimurium for tryptophan, an amino acid not present in flagellar protein. Under these conditions net ribonucleic acid (RNA) synthesis was reduced to approximately 10% of the control rate. Less than 1 ,ug of actinomycin D per ml further reduced RNA synthesis to less than 1 % of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The production of flagellar protein requires the concomitant synthesis of RNA in S . Typhimurium (Aamodt and Eisenstadt, 1968 ). Because polyamines in a polyamine–RNA complex in cells are essential for RNA synthesis and functions (Igarashi and Kashiwagi, 2010 ; Lenis et al, 2017 ), it is reasonably assumed that the unbalanced metabolism of polyamines could interfere with the flagellation of S .…”
Section: Discussionmentioning
confidence: 99%
“…The production of flagellar protein requires the concomitant synthesis of RNA in S . Typhimurium (Aamodt and Eisenstadt, 1968 ). Because polyamines in a polyamine–RNA complex in cells are essential for RNA synthesis and functions (Igarashi and Kashiwagi, 2010 ; Lenis et al, 2017 ), it is reasonably assumed that the unbalanced metabolism of polyamines could interfere with the flagellation of S .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Aamodt and Eisenstadt (1) found that actinomycin D, which inhibits RNA and protein synthesis by 99% in S. typhimurium, prevents flagellar regeneration. These combined results imply that synthesis of flagellar protein is less sensitive than that of other cell proteins to certain inhibitors.…”
Section: Ciation a Similar Argument Holds For G-actin Polymerizationmentioning
confidence: 99%
“…This includes the demonstration of stable membrane-bound polysomes in sporulating Bacillus subtilis (2), Act D-resistant sporulation in B. subtilis (21), and synthesis of penicillinase in the absence of RNA synthesis by B. licheniformis (23,24). Stable mRNA-directed synthesis of B. subtilis (15) and Salmonella typhimurium (14) flagella has been suggested, although further work has indicated that RNA synthesis is indeed required for flagellin synthesis in B. subtilis (8) and in S. typhimurium (1).…”
mentioning
confidence: 99%